Treating the brain deep down: Brain surgery for anorexia nervosa? - Nestler, Eric J (2013)
Using brain surgery, specific areas in the brain can be stimulated with electrical impulses to reversibly change their activity and alleviate symptoms related to mental illnesses. This so-called deep brain stimulation and other methodological advances that even more selectively activate specific group of neurons can give us clues as to what neural circuitry is involved in a particular mental disorder and whether therapeutic activation of these brain areas and neurons may be effective. In ‘Bedside to Bench’, Eric Nestler discusses two trials of individuals with anorexia nervosa in which deep brain stimulation of different brain areas resulted in improvement of behavioral domains associated with the syndrome. The results and potential of this technique in animals and humans may bring us closer to understanding the neurobiology of anorexia nervosa, which still remains a mystery and poses a challenge for treatment. In ‘Bench to Bedside’, Jennifer Warner-Schmidt peruses recent findings that uncover the functional connectivity of brain regions involved in depression and how activation of cortical regions can result in antidepressant effects that can compensate for the malfunction of other brain circuits that results in depression.